Aplikasi Regresi Logistik Ordinal Multilevel untuk Pemodelan Huruf Mutu Mata Kuliah Statistika Dasar Mahasiswa Universitas Islam Bandung Tahun 2019/2020 - Erfina Agustin Hidayat; Nusar Hajarisman (Bandung Conference Series: Statistics, 2023)
Abstract. Multilevel ordinal logistic regression analysis is a regression analysis for discrete-scale responses, especially with a hierarchical ordinal scale. The hierarchical structure indicates that the data analyzed comes from several levels, where lower levels are nested in higher levels. This article will discuss the application of multilevel ordinal logistic regression using the Maximum Likelihood Estimation (MLE) method in the field of education, namely regarding the quality letter of the Basic Statistics course of 2019 Bandung Islamic University students at the Faculty of Engineering, Faculty of Business Economics, and Faculty of Psychology. The results showed that the multilevel ordinal logistic regression model can be used. From the results of testing the significance of parameters partially using the Wald test statistic, it is found that the student gender variable, the student regional origin variable, and the student GPA variable before taking the Basic Statistics course have an influence on the quality letter of the Basic Statistics course. Abstrak. Analisis regresi logistik ordinal multilevel merupakan analisis regresi untuk respon berskala diskrit khususnya dengan skala ordinal yang bersifat hierarki. Struktur hierarki mengindikasikan bahwa data yang dianalisis berasal dari beberapa level, di mana level yang lebih rendah tersarang pada level yang lebih tinggi. Dalam skripsi ini akan dibahas mengenai pengaplikasian regresi logistik ordinal multilevel dengan menggunakan metode Maximum Likelihood Estimation (MLE) di bidang pendidikan yaitu mengenai huruf mutu mata kuliah Statistika Dasar mahasiswa Universitas Islam Bandung 2019 di Fakultas Teknik, Fakultas Ekonomi Bisnis, dan Fakultas Psikologi. Hasil penelitian menghasilkan bahwa model regresi logistik ordinal multilevel dapat digunakan. Dari hasil pengujian signifikansi parameter secara parsial menggunakan statistik uji Wald didapatkan bahwa variabel jenis kelamin mahasiswa, variabel asal daerah mahasiwa, dan variabel IPK mahasiswa sebelum mengambil mata kuliah Statistika Dasar memiliki pengaruh terhadap huruf mutu mata kuliah Statistika Dasar